1995
DOI: 10.3354/meps120163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure and previous exposure to copper on growth of veliger larvae and survivorship of Mytilus edulis juveniles

Abstract: Exposure of Mytilus edulis L. (Molluscs: Bivalvia) to 8 ppb (ppb = 1-lg I-') added copper during the vellger larval or post-larval (spat) stages has no significant effects on survivorship or shell growth However, previous exposure to 8 ppb added copper d u r~n g the embryo stage significantly Increases veliger growth rate and decreases spat survivorship in a population from the Menal S t r a~t , Wales, UK, in which this level of copper causes a slgnlflcant increase in embryo abnormality No such effects of pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…The present study confirms sensitivity of clam larvae to heavy metals as shown by Manahan and Crisp (1982), and can be easily used for field monitoring of water and sediment quality. Many other works showed that heavy metals caused failure in metamorphosis (Beiras and His, 1994;Hoare et al, 1995); this was not shown in our study, where metamorphosis success was not affected but survival was reduced at the end of this step at the Mahres, Zarat, and Monastir stations. However, the use of larvae for bioassay is problematic because sensitivity is age-dependent (Beiras and His, 1994).…”
Section: Discussioncontrasting
confidence: 90%
“…The present study confirms sensitivity of clam larvae to heavy metals as shown by Manahan and Crisp (1982), and can be easily used for field monitoring of water and sediment quality. Many other works showed that heavy metals caused failure in metamorphosis (Beiras and His, 1994;Hoare et al, 1995); this was not shown in our study, where metamorphosis success was not affected but survival was reduced at the end of this step at the Mahres, Zarat, and Monastir stations. However, the use of larvae for bioassay is problematic because sensitivity is age-dependent (Beiras and His, 1994).…”
Section: Discussioncontrasting
confidence: 90%
“…In our analyses, there was no evidence that pollution influenced mussel population structure. This is perhaps surprising, given evidence of severe effects of some pollutants on mussel larvae (Hoare, Beaumont & Davenport 1995; Hoare, Davenport & Beaumont 1995). Nevertheless, the current evidence suggests that the relationship between SFG and community structure is probably driven by direct effects of pollution on the organisms associated with the mussels rather than by indirect effects mediated by changes in the habitat provided by the mussels.…”
Section: Discussionmentioning
confidence: 99%
“…Cu reduced the growth of colonies in both seasons, but more dramatically in winter and only on 2 of 3 panels at 1 site in summer. Hoare et al (1995) suggested that the exposure to Cu could alter the larval physiology, reducing the lipid reserve that is essential for larval metamorphosis and growth. While reduced lipid reserves might account for smaller ancestrulae, it is surprising that such effects persist through several cycles of budding, when budding is fuelled by feeding of many zooids.…”
Section: Discussionmentioning
confidence: 99%